SISTEM INFORMASI PENGELOLAAN DAFTAR KEHADIRAN DAN JADWAL PEMBICARA BERBASIS WEBSITE DENGAN MAIL GATEWAY PADA KOMUNITAS JC BANDUNG - Julian Anugrah Sihite; Meliana Christianti J. (Maranatha University Press, 2017)
Along with the progress of the technology nowadays, there are so many information systems which have already used computerized system. But there are still many companies or organizations out there which have been using manual system until now. One of them is JC Bandung, one of the biggest teens church community in Bandung. They still use manual system to handle their problems. So there are too much troubles to handle both in technically and directly. For example reports of church member attendance and event are still made manually. So this application has been made to fulfill their needs for the community.Â Keywords â€” attendance, church, data management, information system, member